Compressive response of multi-layered thermoplastic composite corrugated sandwich panels: Modelling and experiments. (15th May 2020) - Chen, Liming; Peng, Shiwei; Liu, Jian; Liu, Houchang; Chen, Liliang; Du, Bing; Li, Weiguo; Fang, Daining
Abstract: Multi-layered thermoplastic composite (TPC) corrugated sandwich panels (CSPs) were designed and fabricated from glass fiber reinforced polypropylene prepregs by hot-pressing and hot-melting bonding methods. Quasi-static compressive response including failure deformation modes of TPC CSPs were experimentally and numerically investigated to reveal the effect of layer numbers and core configurations namely regular, perpendicular and symmetrical. For two-layered CSPs, core layers of the regular configuration panels were firstly compressed to overlapping and then failed together, core layers of the perpendicular ones failed step by step. But for the symmetrical configuration, assembly deviations were found to affect the deformation modes sensitively by comparing the experimental and numerical results. Among three configurations, the perpendicular one has the optimal specific energy absorption ( SEA ) and crushing force efficiency ( CFE ), while the regular one has the biggest peak crushing force ( PCF ). Increasing layer number can enhance the SEA and MCF due to the bending of the interlayer face sheets.